Pengembangan Media Lembar Kerja Peserta Didik (LKPD) Berbasis Inkuiri Pada Materi Koloid - Rosalia Wea Tadi Nuwa; Maria Benedikta Tukan; Erly Grizca Boelan; Maria Aloisia Uron Leba; Faderina Komisia; Anselmus Boy Baunsele; Aloysius Masan Kopon (Journal on Education, 2024)
Education is a conscious effort made by humans to achieve their life goals. Student Worksheets (LKPD) are sheets containing tasks that must be carried out by students in order to improve student learning outcomes. LKPD usually contains instructions, steps to complete a task. The tasks ordered in the LKPD must be clear about the basic competencies to be achieved. The aim of this research is to determine the validity of inquiry-based LKPD on colloidal material and to determine the response of class XI students at SMA Plus Santo Albertus Agung Weleun Malaka to inquiry-based LKPD. This type of research is research and development (Research & Development). The material expert validation results obtained were in the very appropriate category with a percentage of 90%, the media expert validation results obtained were in the very appropriate category with a percentage of 92%, and the student response percentage results obtained were a percentage of 88.75%